L’essentialisme stratégique pour une réorganisation de l’espace - Lise Landrin (EchoGéo)
Chaupadi is a Hindu tradition which enacts a number of strict guidelines for the menstruation of women, by keeping them away from the community. The intervention of a Nepalese NGO to eradicate this practice invite to re-read the feminist debates on essentialism, on the difference as well as on the relevance of the category of "woman". Essentialism, as it denotes irrefutable characteristics, has been criticized by different waves of feminists, who rightly insist on the socially constructed significance of the identities. However, if anti-essentialism appropriately disintegrates fixist identities, is it effective for political action? This article questions the validity of the "strategic essentialism" of an NGO that wishes to counter a practice and foster physical and moral integrity of women in a rural area.